Efektivitas Kinerja Ombudsman Republik Indonesia Perwakilan Provinsi Banten Dalam Pengawasan Penyelenggaraan PPDB Tingkat SMA Tahun 2017-2018 - Megawati Putri Pertiwi (Epistemik Press, 2020)
This research explains Effectiveness Performance Ombudsman of Republic Indonesia Representative Banten Province in Supervising of PPDB Implementation for High School 2017-2018. This paper also further discusses Performance Ombudsman of Republic Indonesia Representative Banten Province in exercising his authority overseeing the implementation of PPDB at the secondary school level. The purpose of this research is to determine the effectiveness of performance Ombudsman the Republic of Indonesia Banten Province Representative on Supervising of PPDB Implementation for High School. The theory used in this research is Etzioni's theory of organizational performance effectiveness. This theory uses four assessment indicators namely adaptation. integration, motivation and production. The research method used is descriptive qualitative research method. The results of this research indicate that the supervisory performance carried out by Ombudsman of Republic Indonesia Representative Banten Province in the implementation of the high school level PPDB has not been carried out effectively. This can be seen through the four assessment indicators caused by not being able to make optimal adaptation, integration, motivation and production.